Rb silencing mediated by the down‐regulation of MeCP2 is involved in cell transformation induced by long‐term exposure to hydroquinone. Issue 2 (19th July 2016) - Liu, Linhua; Ling, Xiaoxuan; Wu, Minhua; Chen, Jialong; Chen, Shaoqiao; Tan, Qiang; Chen, Jiansong; Liu, Jiaxian; Zou, Fei
Abstract : Hydroquinone (HQ), a metabolite of benzene, is a well‐known human carcinogen; however, its molecular mechanisms of action remain unclear. MeCP2 has been traditionally described as a transcriptional repressor, though growing evidence indicates that it also activates gene expression. Here, we investigated whether some epigenetic machinery genes are aberrantly expressed as target tumor suppressor genes in HQ‐transformed TK6 lymphoblastoid cells. Our results showed that treatment with 5‐Aza‐2′‐deoxycytidine or trichostatin A enhanced the expression of Rb, resulting in cell arrest in G1‐phase, and subsequently, an increase in apoptosis and a decrease in cell growth. Moreover, we hypothesised that Rb was silenced by the down‐regulation of MeCP2 in HQ‐transformed cells, resulting in the dynamic expression of Rb and epigenetic machinery proteins in HQ‐transformed cells at different time points. The expression of Rb and MeCP2 in patients with B‐cell non‐Hodgkin's lymphoma (B‐NHL) showed that positive staining for MeCP2 or Rb was significantly lower in B‐NHL tumor tissues, and these changes were significantly and negatively correlated with the grade of B‐NHL. The restoration of MeCP2 in HQ‐transformed cells enhanced the expression of Rb, promoted cell apoptosis, and inhibited cell growth. The changes in the expression patterns of MeCP2 and Rb were inversely correlated with the degree of DNA methylation. A ChiP assay revealed that MeCP2 proteins were recruited to the Rb promoter with lower 5′‐methylcytosine levels. In conclusion, we demonstrated that the down‐regulation of MeCP2 silences Rb, a process involved in cell transformation resulting from long‐term exposure to HQ. © 2016 Wiley Periodicals, Inc.